2020
DOI: 10.1111/jcal.12496
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multidimensional polychronicity scale for information technology learning

Abstract: Information technology provides the potential for polychronic learning. However, research on polychronicity in the educational field is scarce. The purposes of this study were to develop a multidimensional polychronicity scale for information technology learning and explore the relationship between polychronicity in information technology‐supported learning and personality traits. This study is divided into two phases. First, a questionnaire survey was used to develop a multidimensional polychronicity scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…SEM for the total sample showed that The test failed to obtain nonsignificant results, likely because the value is sensitive to the number of cases ( Bergh, 2015 ). Therefore, in large samples, the value may not be an appropriate indicator, and alternative indicators will be needed ( Luo et al, 2021 ). Other indicators used in this study showed that χ 2 / df = 4.74, TLI = 0.92, CFI = 0.93, and RMSEA = 0.07, all satisfying the following criteria: χ 2 / df < 5 ( Jöreskog and Sörbom, 1993 ), TLI > 0.90 ( Bentler and Bonett, 1980 ), CFI > 0.90 ( Li, 2006 ), and RMSEA < 0.08 ( McDonald and Ho, 2002 ), indicating that the fit between the model and the observed data was good.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SEM for the total sample showed that The test failed to obtain nonsignificant results, likely because the value is sensitive to the number of cases ( Bergh, 2015 ). Therefore, in large samples, the value may not be an appropriate indicator, and alternative indicators will be needed ( Luo et al, 2021 ). Other indicators used in this study showed that χ 2 / df = 4.74, TLI = 0.92, CFI = 0.93, and RMSEA = 0.07, all satisfying the following criteria: χ 2 / df < 5 ( Jöreskog and Sörbom, 1993 ), TLI > 0.90 ( Bentler and Bonett, 1980 ), CFI > 0.90 ( Li, 2006 ), and RMSEA < 0.08 ( McDonald and Ho, 2002 ), indicating that the fit between the model and the observed data was good.…”
Section: Resultsmentioning
confidence: 99%
“…That is, people who prefer to work in a timely, timesaving, and schedule-based manner actually participate in more tasks simultaneously and experience higher satisfaction in the process of using digital technology to learn. Luo et al (2021) and Nonis et al (2005) pointed out that “time tangibility,” which is closely related to time management, enables people to complete tasks on time or even deal with more tasks, and it is in line with the online learning environment that requires learners to perform learning tasks in a polychronic manner ( Lee and Perry, 2001 ; Capdeferro et al, 2014 ; Lepp et al, 2019 ). Finally, the “involvement with people” aspect of polychronicity in online learning did not predict “knowledge acquisition.” It is possible that although emerging IT has multiple interpersonal interaction functions, Taiwanese students still seldom use these interactive functions in IT-supported learning, possibly because obedience and silence in classroom learning have long been aspects of the learning culture of Chinese students ( Luo and Yang, 2018 ), which may extend to virtual online learning environments.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations